THE INFLUENCE OF ENGLISH SONG AS LEARNING MEDIA TOWARDS STUDENT LEARNING MOTIVATION AND LEARNING ACHIEVEMENT IN LEARNING ENGLISH - Aisyah Frida Rahmania; Sri Handayani; Luqman Al Hakim (LPPM Universitas PGRI Jombang, 2025)
This research was aims to find out the influence of English Song as learning media towards student learning motivation and learning achievement in learning English at the eleventh grade students of MAN 1 Surakarta at the 2024/2025 academic year. This research used Quantitative method. The sample of this research was 26 students. The researcher used a Questionnaire to find out the students learning motivation, and Test used to find out the learning achievement. The result of this research indicate there is significance influence of English Song as learning media towards students learning motivation and learning achievement in learning English. It is proven by the result after analyzing the data using paired sample t-test formula with the help of IBM SPSS Statistics 25. The result of the tcount for questionnaire = 26.738 > 2.060, and tcount for test = 12.127 > 2.060. Both of the result tcount are greater than the ttable then Ho is rejected and Ha is accepted. So it can be conclude that there is significance influence of English Song as learning media towards student learning motivation and learning achievement in learning English at the eleventh grade students of MAN 1 Surakarta at the 2024/2025 academic year.